MODEL PEMBELAJARAN CORE, SCRAMBLE, HASIL BELAJAR, DAN OPERASI HITUNG BENTUK ALJABAR - Ilela, Nathalia; Laamena, Christina Martha; Tamalene, Hanisa (Universitas Papua, 2021)
The learning model has an essential role in student learning outcomes. Each learning model has different contributions, such as the Scramble learning model, which can make students think quickly, and the CORE learning model can train students to think critically. Thus, this study aims to compare students' learning outcomes with the two models, especially in arithmetic operations in algebraic forms. The research method used is quantitative research with a posttest-only group design classified as a quasi-experimental design. The research population was forty-five seventh-grade students, which were divided into two categories. The test instrument used is a description of five questions used to evaluate student learning outcomes. The study results analyzed statistically using the t-test showed that there were differences in student learning outcomes between the two groups of students. Furthermore, the continued test using Pairwise Comparison showed that students taught with the Scramble learning model had better learning outcomes than students acquainted with the CORE learning model.